2017
DOI: 10.2147/eect.s69854
|View full text |Cite
|
Sign up to set email alerts
|

A new bioenergy crop based on oil-rich seeds from the legume tree <em>Pongamia pinnata</em>

Abstract: Any informed discussion on the future sources of energy in our world requires the consideration of renewable biofuels. These are produced by biological processes, such as plant growth based on photosynthesis and microbes using waste products from diverse origins. Many biofuels, such as ethanol produced from plants like sugarcane, are seen as sustainable, such paradigms should be critically analyzed in terms of total inputs. The legume tree Pongamia pinnata (also called Millettia pinnata) offers a substantiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Alternatively, ecological restoration of the metal-infested cultivable/fertile land with hyperaccumulator bioindicator species (plants with a remarkable capacity of accumulating particular HMs/metalloids within their body tissues that are hundred to thousand folds higher than other usual species of plants) [ 73 – 75 ], as listed in [ 76 ], can be done. Hyperaccumulating biodiesel/bioenergy crops with oil-rich seeds (e.g., leguminous plants like Pongamia pinnata and Brassica juncea ) [ 77 , 78 ] can also be applied for ecorestoration of the study site. It is noteworthy that ecorestorative studies on EKW have not been previously reported, neither PGPR-assisted ecorestorative strategies been earlier proposed by any research groups.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Alternatively, ecological restoration of the metal-infested cultivable/fertile land with hyperaccumulator bioindicator species (plants with a remarkable capacity of accumulating particular HMs/metalloids within their body tissues that are hundred to thousand folds higher than other usual species of plants) [ 73 – 75 ], as listed in [ 76 ], can be done. Hyperaccumulating biodiesel/bioenergy crops with oil-rich seeds (e.g., leguminous plants like Pongamia pinnata and Brassica juncea ) [ 77 , 78 ] can also be applied for ecorestoration of the study site. It is noteworthy that ecorestorative studies on EKW have not been previously reported, neither PGPR-assisted ecorestorative strategies been earlier proposed by any research groups.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In recent decades, the world has recorded an uncontrolled and unprecedented use of fossil fuels which has significantly increased greenhouse gas emissions, global climate change, and health-related hazards. Thus, alternative energy sources are being investigated [21][22][23][24][25]. The alternative renewable sources of fossil energy such as wind, solar, hydropower, geothermal, and biomass are considered vital for reducing the dependence on fossil fuels and the environmental concern, as well as for coping with global climate change [22,23].…”
Section: Introductionmentioning
confidence: 99%